Design and implementation of flexible advanced training in rheumatology: report of a pilot programme. Issue 10 (2nd June 2022) - Anandacoomarasamy, Ananthila; Richards, Bethan; Ward, Louise; Langford, Kiri; Wallace, Genevieve; Sinclair, Tim; Anderson, Teresa; Barnsley, Les
Abstract: Background: Training in medicine is highly demanding and coincides with critical life tasks including relationship development, childbearing and rearing. The rigid requirements of training programmes risk precluding successful achievement of these extracurricular roles, forcing choices between work and other life commitments. Flexible employment structures that facilitate the development of high‐quality physicians are needed. Aim: To assess the outcomes of 2 novel flexible training positions in Rheumatology. Methods: The clinical department, trainees and senior administration designed flexible, part‐time advanced training positions in rheumatology. We sought to deliver excellent training, supervision and support while ensuring safe, efficient clinical service delivery within existing systems and cultures. Barriers to implementation were actively identified. We rejected job share arrangements in favour of independent part‐time positions anchored to departmental education, clinical and trainee needs. The outcomes of these positions have been determined through regular trainee meetings, clinic activity and costs. Results: Trainees achieved all training requirements, reported high levels of job satisfaction, strong professional development, improved work−life balance and reduction of stress. Outpatient events increased and waiting times have decreased. We estimate that increased rebatable outpatient services have rendered the positions cost neutral. Conclusion: Flexible training positions can enhance clinical departments while enabling high‐quality training for junior doctors. Further work should consider longer term outcomes and application to different clinical and training settings.